2018
DOI: 10.1002/da.22839
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of comorbid anxiety disorders on treatment outcome in a randomized controlled psychotherapy trial in early-onset persistently depressed outpatients

Abstract: Patients suffering from PDD comorbid with AD might experience greater benefit when they are treated with specific as opposed to unspecific therapy. Analyzing subgroups of patients with PDD seems worthwhile to improve treatment effectiveness even within disorder-specific treatment programms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…This RCT demonstrated that, in unmedicated Future studies should examine moderators of this sequential mediation. For example, the effect could be particularly prominent in certain subpopulations, such as patients reporting early emotional abuse or patients suffering from comorbid social anxiety, because these subgroups benefitted most from CBASP in this trial [5,6]. These variables are also important in the CBASP model because interpersonal fear avoidance mediates the association between emotional abuse and specific social skill deficits in PDD [7].…”
Section: Karger@kargercommentioning
confidence: 99%
“…This RCT demonstrated that, in unmedicated Future studies should examine moderators of this sequential mediation. For example, the effect could be particularly prominent in certain subpopulations, such as patients reporting early emotional abuse or patients suffering from comorbid social anxiety, because these subgroups benefitted most from CBASP in this trial [5,6]. These variables are also important in the CBASP model because interpersonal fear avoidance mediates the association between emotional abuse and specific social skill deficits in PDD [7].…”
Section: Karger@kargercommentioning
confidence: 99%
“…It also remains to be seen if the same results emerge if psychotherapy is conducted in an individual format as opposed to group format and if CBASP or MBCT are compared with other forms of psychotherapy. Results of a recent study comparing CBASP as an individual therapy with supportive psychotherapy in patients with chronic depression, however, suggests that individual CBASP as well is particularly effective for nonassertive patients, since comorbid social anxiety moderated outcomes in favor of CBASP (Assmann et al, 2018). Furthermore, more research is necessary to explore whether interpersonal problems moderate intervention effects on other outcome or process variables like the therapeutic alliance (Mander et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The self-rating socio-demographic questionnaire was adapted from the version developed by the Epidemiology Department of Harbin Medical University and was used to collect detailed background information on family psychiatric history, childhood trauma history, and socioeconomic background. The HRSD-24 ( 23 ) is widely used to measure depression symptoms; ( 24 26 ) a number of patients above the threshold (21 points) were included in the study. The LES questionnaire for measuring negative life events contained 48 items in three dimensions: family life (28 items), work-related problems (13 items), and social and other aspects (seven items).…”
Section: Methodsmentioning
confidence: 99%